Chiral Dihydrobenzofuran Acids Show Potent Retinoid X Receptor-Nuclear Receptor Related 1 Protein Dimer Activation - Sunden, Henrik; Schafer, Anja; Scheepstra, Marcel; Leysen, Seppe; Malo, Marcus; Ma, Jian-Nong; Burstein, Ethan S.; Ottmann, Christian; Brunsveld, Luc; Olsson, Roger (Journal of medicinal chemistry, 2016)
The nuclear receptor Nurr1 can be activated by RXR. via heterodimerization (RXR Nurr1) and is a promising target for treating neurodegenerative diseases. We herein report the enantioselective synthesis and SAP, of sterically constricted benzofurans at RXR The established SAR, using whole cell functional assays, lead to the full agonist 9a at RXR. (pEC(50) of 8.2) and RXR-Nurr1. The X-ray structure shows enantiomeric discrimination where 9a optimally addresses the ligand binding pocket of RXR.